`f(x) = x^3 - 2x + 3x^-3` Find the derivative of the function.

Textbook Question

Chapter 2, 2.2 - Problem 40 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

kalau's profile pic

kalau | (Level 2) Adjunct Educator

Posted on

Use the power rule for each term.  Derive each term.

`d/dx x^n= nx^(n-1)`


`f'(x) = 3x^2 -2 -9x^-4`

Eliminate all negative exponents.

The answer is:

`f'(x) = 3x^2 -2 -9/x^4` 

We’ve answered 319,627 questions. We can answer yours, too.

Ask a question